"Recovery of Iron Coagulants From Tehran Water-Treatment-Plant Sludge for Reusing in Textile Wastewater Treatment" - F Vaezi; F Batebi (Tehran University of Medical Sciences, 2001)
Most of the water treatment plants in Iran discharge their sludge to the environment whithout consideration of possible side effects. Since this kind of sludge is generally considered pollutant, the sludge treatment of water industry seems to be an essential task. Obviously theweight and volume of solids produced during the coagulation process are much more than other wastes of water treatment operations, and their treatment is much more difficult as well. Besides, this sludge contains metal hydroxide so disposing of it would waste considerable amounts of valuable metal salts. To face the mentioned problems, reclamation of coagulatns from waste sludges for reuse has been investigated in this research. Among different chemicals used in the experiments of recovery, sulfuric-acid showed better results from both practical and cost viewpoints. Three important phenomena were observed by sludge acidificantion: dissolution of metal hydroxide, reduction of sludge volume and finally faster settleability and dryness of remainder sludge. The salt recovered by sulfuric acid from the sludges of Tehran Water-Treatment Plant was ferric sulfate which showed good results in the treatment of two different types of wastewaters from textile industry.